2021
DOI: 10.3390/met11111861
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition Properties of Thiazolidinedione Derivatives for Copper in 3.5 wt.% NaCl Medium

Abstract: Copper is the third-most-produced metal globally due to its exceptional mechanical and thermal properties, among others. However, it suffers serious dissolution issues when exposed to corrosive mediums. Herein, two thiazolidinedione derivatives, namely, (Z)-5-(4-methylbenzylidene)thiazolidine-2,4-dione (MTZD) and (Z)-3-allyl-5-(4-methylbenzylidene)thiazolidine-2,4-dione (ATZD), were synthesized and applied for corrosion protection of copper in 3.5 wt.% NaCl medium. The corrosion inhibition performance of teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 39 publications
0
1
0
1
Order By: Relevance
“…Permukaan logam bereaksi terhadap suhu, udara, dan gesekan udara sehingga terjadi perubahan pada kondisi fisik logam. Permukaan logam yang mengalami reaksi kimia akan mengalami kerusakan dan penurunan kualitas [4][5][6]. Korosi pada logam sangat dipengaruhi oleh zat-zat yang bersifat asam [7][8][9].…”
Section: Pendahuluanunclassified
“…Permukaan logam bereaksi terhadap suhu, udara, dan gesekan udara sehingga terjadi perubahan pada kondisi fisik logam. Permukaan logam yang mengalami reaksi kimia akan mengalami kerusakan dan penurunan kualitas [4][5][6]. Korosi pada logam sangat dipengaruhi oleh zat-zat yang bersifat asam [7][8][9].…”
Section: Pendahuluanunclassified
“…Recent experiments on corrosion [22][23][24][25] have shown that benzimidazole derivatives possess corrosion-inhibiting properties (Figure 1). According to the literature, most organic compounds are effective corrosion inhibitors, which are widely used to protect copper alloys against corrosion in aqueous environments [22][23][24][25][26][27][28]. Analogous compounds were employed as corrosion inhibitors for copper in a 3.5 wt.% NaCl solution at a temperature of 25 • C. The results suggest that introducing a nitrogen atom into the imidazole ring enhances the inhibitory effect, which is mainly due to the heightened adsorption energy.…”
Section: Introductionmentioning
confidence: 99%